An evaluation of festival activities as motives for festival attendance: A case study of Strawberry festival at the Redberry farm in George, South Africa. - Dr Takalani Ramukumba (African Journal of Hospitality, Tourism and Leisure, 2017)
The author asserts that It is imperative that festival organisers understand tourist motivations for attending festivals in order to conduct effective festival planning and furthermore, in order to achieve a more productive festival marketing position and marketing strategy. The purpose of this study was to evaluate festival activities as motives to attend the Strawberry festival in George, South Africa and as a basis for informing marketing and management recommendations aimed at improving the festival experience of visitors. Much research has been conducted around festival-scape factors, however this study opted to focus on specific festival activities that were used in the promotional and advertising material for the festival, breaking the mould of analysing festival attendance motives as previously employed by many studies. The motivation of these attendees is broken down and viewed abstractly from different viewpoints of how the motivation to attend a festival, differs between attendees of varying age, first-time versus repeat visitors, spending patterns, and satisfaction with the range of services that are provided.